Development of Tree Determination Key for Android Smartphone - Yunita Puspitasari (Buletin Eboni, 2019)
Indonesian forest consists of thousands of tree species. In the field, forest inventory officers need a tool, which can be carried easily, to identify tree species (tree determination key). Accordingly, a smartphone can be used as an alternative. The application selected for constructing the tree determination key was Carrymap Observer, a free and open source application based on Android. Development of database was carried out in a computer using ArcGIS’s plugin namely Carrymap by examining the appropriate text file format and image file size. The identification of tree species was mainly based on leaf characteristics. Those characteristics were used as attributes on point data vector. The utilization of tree determination key on smartphone can facilitate users to identify tree species in the field.